Efektivitas Terapi Spritual Shalat dan Dzikir terhadap Kontrol Diri Klien Penyalahgunaan Napza - Akhmad Akhmad; Indriono Hadi; Askrening Askrening; Ismail Ismail (Health Information : Jurnal Penelitian, 2019)
Religion is one of the protective factors that provides positive results by preventing individuals from engaging in drug abuse. Religion and spirituality can inhibit addiction, and maintain self-control in drug abuse clients. Narcotics that are used continuously will result in a fairly high tolerance, and if the use is stopped it will cause with drawl or withdrawal syndrome. Healing is by means of medical and non-medical rehabilitation, non-medical rehabilitation, one of which is by means of spiritual healing techniques including prayer and dhikr, appearing as a valid Islamic spiritual healing method which is carried out by getting closer to the client to his spirituality and religion. The results of this study, on the pretest measurement results 16 respondents had negative self-control and 12 respondents had positive self-control, then after being given prayer and dzikir therapy treatment for two months, 26 respondents had positive self-control and 2 respondents had negative self-control. Mc Nemar statistical test p value <0.001 less than the value? 0.05, which means that there is an effect of the provision of prayer therapy accompanied by dhikr on client self-control of drug abuse.